2013
DOI: 10.1177/0091270012447196
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Prescribing Patterns and Therapeutic Drug Monitoring of Intravenous Busulfan in Pediatric Hematopoietic Cell Transplant Recipients

Abstract: Personalizing intravenous (IV) busulfan doses in children using therapeutic drug monitoring (TDM) is an integral component of hematopoietic cell transplant. The authors sought to characterize initial dosing and TDM of IV busulfan, along with factors associated with busulfan clearance, in 729 children who underwent busulfan TDM from December 2005 to December 2008. The initial IV busulfan dose in children weighing ≤12 kg ranged 4.8-fold, with only 19% prescribed the package insert dose of 1.1 mg/kg. In those chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 33 publications
2
42
0
2
Order By: Relevance
“…Unfortunately, the current dosing method of using body weight for dose 1 IV busulfan dose rarely achieves the target AUC. Specifically, using body weight to determine dose 1 of IV busulfan results in only 24% of children (McCune et al 2013) and 23% of adults (Yeh et al 2012) achieving their personalized target IV busulfan AUC.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the current dosing method of using body weight for dose 1 IV busulfan dose rarely achieves the target AUC. Specifically, using body weight to determine dose 1 of IV busulfan results in only 24% of children (McCune et al 2013) and 23% of adults (Yeh et al 2012) achieving their personalized target IV busulfan AUC.…”
Section: Introductionmentioning
confidence: 99%
“…9 Studies of Bu kinetics revealed that oral Bu is erratically absorbed and that oral administration of a fixed-dose results in wide variations in plasma Bu levels. 10,11,12,13 Low plasma levels are associated with increased risks of graft-failure and relapse and high levels with increased toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Other than 2 patients for whom test dose PK data were not available, all other patients in our study received either an upward or downward adjustment after the test dose to achieve the total AUC desired, indicating the practicality of the use of the test dose PK results to optimize total Bu exposure. The test doseebased Bu adjustment strategy described thus represents a rational and effective way to address the problem of high variability associated with Bu administration [23]. Data currently available from PK studies of i.v.…”
Section: Discussionmentioning
confidence: 99%